Factores asociados al estrés académico en estudiantes entre 12 a 16 años en la Institución Educativa Juan José Nieto de Baranoa en el periodo 2023-2 (2024)
Academic stress is a reaction of physiological, emotional, cognitive, and behavioral activation to stimuli that occurs in the world, because students are subjected to high levels of pressure because of evaluations and exams, overload of academic tasks and the lack of time to develop activities. The objective of this research was to determine the factors associated with academic stress in students between 12 and 16 years old at the Juan José Nieto Educational Institution of Baranoa in the period 2023-2. Method: A methodology with a positivist paradigm, quantitative, correlational, and transversal approach was proposed, using a simple random sampling, with a sample of 203 students; the instruments used for the study were the Sisco Inventory SV-21, the Family Functioning Scale FACES III, DASS-21, Stroop Test of colors and words, Trail Making Test and the verbal fluency test FAS. Results: 59.1% of the sample were female, 23.6% were between 13 and 14 years old, 43.3% had a positive relationship with their group tutors. Moderate levels of depression, anxiety and stress were found, as well as compromise in cognitive flexibility. The linear regression model indicates that stress, depression, and type of family adaptability are directly associated with students' academic stress. Conclusions: There is a need to develop differentiated and personalized strategies to address stress based on associated variables, recognizing that experiences and needs may vary among specific groups within the student population.